Linguistic Reconciliation in a New Sri Lanka - Perera, N. (University of Jaffna, 2025)
In multicultural and multilingual societies across the globe, the language question has been central to notions of unity and equity. This is especially so in contexts of war based on ethnolinguistic division. Sri Lanka has had a history of linguistic injustice and denial of minority language rights, which both preceded and fed into its 26-year civil war. In the post war period, processes of transitional justice need to be oriented to the central role of language as a part of reconciliation.This talk draws attention to the notion of linguistic reconciliation and examines how it contributes to post-war peacebuilding in Sri Lanka. As the country enters a new post-war phase, with the election of its first leftist government, it is timely to consider the possibilities for achieving linguistic reconciliation amongst the many pressing areas in need of reform. The presentation is comprised of two qualitative studies: 1. A study on an online adult Tamil language course in Sri Lanka which involved qualitative interviews with students and teachers of varying ethnicities and language backgrounds. Reflexive thematic analysis of interview transcripts was used to understand the influence of language politics, war and trauma, and language policy on learners’ motivations to study Tamil. Results showed that learners’ motivations extended beyond the norm of the instrumental/integrative dichotomy and revealed the role of social, historical, and political influences and a shared vision for societal multilingualism. The results helped to form a preliminary conceptualisation of linguistic reconciliation and to promote language learning “of the enemy” as an integral and impactful component. 2. A pilot study to understand the future for language rights and linguistic reconciliation in a ‘new’ Sri Lanka. This study is based on interviews with key language stakeholders in Sri Lanka to gain their historical perspective on the journey for language rights following the Lessons Learnt and Reconciliation Report in 2011 and into the first six months of the new national leadership. This study is in the preliminary phase, so initial impressions will be offered. This talk aims to provide an overview of how language politics have played out in Sri Lankan society in recent history and generate discussion regarding the advancement of minority language rights into the near future, under a new political regime.
Keywords: Linguistic justice; Transitional justice; Reconciliation; Language rights; Tamil